REPRESENTATION OF ROMANTIC IN THE FILM “IF I STAY” MOVIE (Karya Ilmiah Mahasiswa (KIMA), 2024)
This study aims to describe (1) What is behind the Romantic in the film If I Stay. (2) How Romantic is in the film If I Stay. The object in this study is the film If I which was filmed in 2014 and directed by R. J. Cutler and produced by Denise Di Novi and Alison Greenspan, the script of the film was written by Shauna Cross based on the novel If I Stay by Gayle Forman. The Research Method uses a qualitative descriptive design to analyze the background and romantic problems in this film. The results in this study are to describe the true love story contained in the film If I Stay. The results of the analysis in this study are only taken from a few quotes, focusing on the story, expression and emotional reaction in the character. The conclusion in this study is that there is eternal love, a symbol of the loyalty and sincerity of love from a character of Adam and Mia, and vice versa. Thus, the sincerity of love the story depicted in the film also depicts the implied expressions on Adam and Mia. Deep emotion because of the love that ends happily and sincerely